Incidence of Bacteremia and Septicemia in patients attending in tertiary care center, Nepal - Chaudhary, R; Karmacharya, S; Shrestha, S; Dahal, RK; Mishra, SK; Banjade, NR; Kattel, HP; Rijal, BP; Sherchand, JB; Pokhrel, BM (Journal of Institute of Medicine Nepal, 2013)
Introduction: Bacteremia and septicemia is life threatening condition resulting in major cause of mortality and morbidity.The aim of study was to determine the etiology of bacteremia and septicemia with antibiotic sensitivity profile of those organisms. Methods: A prospective study was carried out among the suspected cases from both inpatient and outpatient of TUTH from October 2009 .March 2010. Blood samples were collected and processed according to standard methodology. Results: Out of 2259 samples only 237 (10.49 %) showed bacterial growth. The most common isolates among Salmonella group was Salmonella enterica serotype typhi 71(29.95%) followed by Salmonella enterica serotype Paratyphi A 45(18.98%). Among non Salmonella group Pseudomonas aeruginosa 34(14.34%), Klebsiella pneumoniae 22(9.28%), Acinetobacter spp 15 (6.32%), Citrobacter spp 5(2.10%), Escherichia coli 3(1.26%) while Staphylococcus aureus 34 (14.3%) was most common followed by Enterococcus spp 3(1.26%), Streptococcus spp 2(0.84%), Coagulase Negative Staphylococcus 2(0.84%) and Listeria spp 1(0.42%) among Gram Positive organisms. Antibiogram revealed Cefotaxime, Ceftazidime, Azithromycin and Chloramphenicol for Salmonella group while for non Salmonella Imipenem, Meropenem and Amikacin as most effective antibiotics while Clindamycin, Cipro!oxacin and O!oxacin for gram positive. Conclusion: Gram negative bacteria was the predominant organism causing bacteremia and septicemia. Among them salmonella typhi and salmonella paratyphi were the leading aetiology. DOI: http://dx.doi.org/10.3126/joim.v34i3.8915 Journal of Institute of Medicine, December, 2012; 34:32-38